The Effect of Green Chemistry-Integrated Project-Based Learning on Students' Learning Outcomes in Acid-Base Chemistry - Devi Septyani Ginting; Dewi Syafriani (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aimed to determine whether students taught using the Green Chemistry-Integrated Project-Based Learning (PjBL) model achieved better learning outcomes than students taught using the Direct Instruction (DI) model on acid-base material. This study used a quasi-experimental method with a nonequivalent control group design. The sample consisted of two eleventh-grade classes at SMAN 1 Sei Bingai, with 32 students in each class. The experimental class was taught using Green Chemistry-Integrated PjBL, while the control class was taught using DI. The research instrument was a 20-item multiple-choice test on acid-base material. The data were analyzed using normality test, homogeneity test, independent sample t-test, and Cohen’s d effect size analysis. The results showed that the experimental class obtained a higher posttest score (83.91 ± 10.13) than the control class (77.81 ± 11.31), with p = 0.029 < 0.05. The effect size was 0.56, which is categorized as a medium effect. These findings indicate that the Green Chemistry-Integrated PjBL model significantly improved students' learning outcomes in acid-base chemistry compared to the Direct Instruction model.